PENGARUH PENERAPAN ICEBREAKER GAMES PESAN BERANTAI TERHADAP KETERAMPILAN MENYIMAK BAHASA ARAB SISWA - Lestari, Heni Widiya; Ghozali, Solchan (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Listening skills are communication activities that aim to receive information from other people with personal interpretation. By practicing listening, students can develop concentration and elements that can develop through subsequent activities such as reading, speaking and writing. It is hoped that the use of chain message ice breaking games, which has become the center of attention in research on listening skills, can be a solution to motivate and encourage students. In this way, they can feel happy following lessons in class and gain knowledge effectively. Quantitative research methods involve the use of data in the form of numbers and the application of statistical analysis. One efficient form of quantitative research design is experimental research, which is used to test hypotheses and control certain variables through treatment. In the context of experimental design, researchers can compare groups of subjects who receive treatment with groups who do not receive treatment. The application of the Chain Message Icebreaker Games to class IV students at MI At-Taqwa Kebonagung Sukodono Sidoarjo was categorized as "Good" based on the average score obtained. It is known that the average score of the control post-test is 69.85, while the average score of the experimental post-test is 75.30, which is included in the "Good" category. The Arabic listening skills of class IV students at MI At-Taqwa Kebonagung Sukodono Sidoarjo are also in the "Good" category. This can be seen from the average score for the experimental group of 60.80, while the control group reached 53.20, with a difference of 7.6 (60.80-53.20).